PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN MEMBELI DI J.CO DONUTS DAN COFFE PALU GRAND MALL - LISTANTO, DEDE KURIANG (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study aims to know the influence of service quality and price to consumen satisfaction at J.CO Donuts and Coffe Palu Grand Mall. Total sample in this study are 60 respondent, with Purposive sampling as sampling technique. Data analysis methode used in this research is Multiple Linear Regression Analysis. The result shows that service quality and price simultaneously have a signifikan influnce to consument satisfaction at J.CO Donuts and Coffe Palu Grand Mall. Service quality partially have a signifikan influence to consument satisfaction at J.CO Donuts and Coffe Palu Grand Mall. Price partially have a signifikan influence to consument satisfaction at J.CO Donuts and Coffe Palu Grand Mall.Keywords: Service quality, price, consumen satisfaction